Debating the Reformation - Leonard, Amy (The sixteenth century journal, 2018)
This article presents an essay written by historian Amy E. Leonard on the topic of teaching about the Protestant Reformation. She comments on the importance of understanding the religious background and emotional aspects of the religious movement and the subsequent Catholic Counter-Reformation. She also offers teaching methods and strategies to further engage students.